Wait and snap: eastern snapping turtles (Chelydra serpentina) prey on migratory fish at road-stream crossing culverts. (30th September 2020) - Alcott, Derrick; Long, Michael; Castro-Santos, Theodore
Abstract : There is growing evidence that culverts at road-stream crossings can increase fish density by reducing stream width and fish movement rates, making these passageways ideal predator ambush locations. In this study, we used a combination of videography and δ 13 C stable isotope analyses to investigate predator–prey interactions at a road-stream crossing culvert. Eastern snapping turtles ( Chelydra serpentina ) were found to regularly reside within the culvert to ambush migratory river herring ( Alosa spp.). Resident fish species displayed avoidance of the snapping turtles, resulting in zero attempted attacks on these fish. In contrast, river herring did not display avoidance and were attacked by a snapping turtle on 79% of approaches with a 15% capture rate. Stable isotope analyses identified an apparent shift in turtle diet to consumption of river herring in turtles from culvert sites that was not observed in individuals from non-culvert sites. These findings suggest that anthropogenic barriers like culverts that are designed to allow passage may create predation opportunities by serving as a bottleneck to resident and migrant fish movement.